Staphylococcus aureus Nasal Colonization: An Update on Mechanisms, Epidemiology, Risk Factors, and Subsequent Infections - Sakr, Adèle; Brégeon, Fabienne; Mège, Jean-Louis; Rolain, Jean-Marc; Blin, Olivier (Frontiers in Microbiology, 2018)
Up to 30 % of the human population are asymptomatically and permanently colonized with nasal Staphylococcus aureus. To successfully colonize human nares, S. aureus needs to establish solid interactions with human nasal epithelial cells and overcome host defense mechanisms. However, some factors like bacterial interactions in the human nose can influence S. aureus colonization and sometimes prevent colonization. On the other hand, certain host characteristics and environmental factors can predispose to colonization. Nasal colonization can cause opportunistic and sometimes life-threatening infections such as surgical site infections or other infections in non-surgical patients that increase morbidity, mortality as well as healthcare costs.